Pengaruh Pupuk Organik Terhadap Perbaikan Struktur Dan Stabilitas Tanah - Mendrofa, Marta Tristanti; Gulo, Dencervis (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This research aims to evaluate the effect of organic fertilizer on improving soil structure and stability. In this research, soil taken from local agricultural locations was processed with the addition of organic fertilizer consisting of compost and manure. The parameters measured include soil porosity, aggregate stability, water absorption capacity and nutrient availability. The results show that the application of organic fertilizer significantly increases soil porosity by 20%, aggregate stability by 30%, and water absorption capacity by 25%. Apart from that, nitrogen, phosphorus and potassium levels also increased after treatment. These findings indicate that organic fertilizers not only improve soil physical structure but also increase soil fertility, which is important for agricultural sustainability. This research suggests the use of organic fertilizer as an effective alternative to improve soil quality in agricultural practices.